Analysis of Factors Affecting Leverage in Manufacturing Companies Listed on the Indonesia Stock Exchange - Arni Maharani (Eastasouth Institute, 2022)
This study aims to examine the factors that affect leverage, as measured by profitability, liquidity, asset tangibility, growth opportunity, company size, business risk, and free cash flow. Profitability is measured by return on assets, and liquidity is measured by the current ratio in influencing leverage. The population used in this study were 438 manufacturing companies listed on the Indonesia Stock Exchange for the period 2012-2015. The research sample was selected using a purposive sampling method so that 208 manufacturing companies were found that met the criteria. Data analysis in this study used multiple regression. The results showed that profitability and liquidity had a significant negative effect on leverage, growth opportunity had a positive effect on leverage, and firm size has a positive effect on leverage. Meanwhile, asset tangibility, business risk, and free cash flow do not affect leverage.